(untitled) (Vietnam Journal of Community Medicine, 2021)
The study was conducted to compare disease patterns and some related factors at request-based polyclinic department, National lung hospital in epidemic year 2020 and disease-free year 2018. A cross-sectional investigation study, comparing from records of 111,796 patients who came to the clinic for outpatient examination and treatment from January 2018 to December 2018 and from January 2020 to December 2020. Research results show that the disease structure in request-based polyclinic is respiratory disease, however, other specialized diseases are also increasing, especially reflux disease, which accounts for a very high rate. During the epidemic period, the number of patients coming to the clinic decreased, but the rate of patients coming to the hospital increased.. This result is the basis for building equipment, communication and training human resources to improve the quality of healthcare services. clinic to meet the needs of the people as well as the quality of examination and treatment at National Lung Hospital in normal and epidemic times.